Emergency care provision at the 2009 Special Olympics Great Britain. Issue 5 (5th May 2012) - Williamson, Timothy; Wheeler, Patrick; Stephens, Catherine; Ferguson, Mike
Abstract : Background: The Special Olympics Great Britain (SOLGB) summer games 2009 were held in Leicester between 25 and 31 July. They involved 2413 athletes that were engaged in 21 different sports across 19 different locations. The onsite healthcare was provided by a specialist medical team. The hospital services available were at the local emergency department (ED) and the co-located urgent care centre (UCC). Aim: To assess the on-site provision required to support a large multisport event for people with learning disabilities and to ascertain the impact on the local hospital services. Methods: On-site consultations were documented on SOLGB medical record forms. Referrals to the local ED and UCC were identified from the SOLGB medical notes or from the ED/UCC attendance codes, as a specific code was applied to all patients related to the games. Results: 581 on-site consultations were documented at SOLGB 2009, of which 95% of these were for athletes. 477 treatments were completed in total, of which 444 were undertaken on-site (93%). 20 people attended the ED; there were no documented attendances at the UCC. 17 of the 20 attendances at the ED were athletes competing. Conclusion: Allocation of the healthcare team was appropriate, with the exception of one sport, where a doctor was moved from a nearby event to consult on 13 occasions. Attendances to the local ED and UCC were minimal. Therefore, the model of on-site medical care that was used, which led to minimal impact on NHS resources, will support the arrangements of medical requirements at future SOLGB games.